Mesoporous Metal–Nitrogen-Doped Carbon Electrocatalysts for Highly Efficient Oxygen Reduction Reaction - Liang, Hai-Wei; Wei, Wei; Wu, Zhong-Shuai; Feng, Xinliang; Müllen, Klaus (Journal of the American Chemical Society, 2013)
A family of mesoporous nonprecious metal (NPM) catalysts for oxygen reduction reaction (ORR) in acidic media, including cobalt–nitrogen-doped carbon (C–N–Co) and iron–nitrogen-doped carbon (C–N–Fe), was prepared from vitamin B12 (VB12) and the polyaniline-Fe (PANI-Fe) complex, respectively. Silica nanoparticles, ordered mesoporous silica SBA-15, and montmorillonite were used as templates for achieving mesoporous structures. The most active mesoporous catalyst was fabricated from VB12 and silica nanoparticles and exhibited a remarkable ORR activity in acidic medium (half-wave potential of 0.79 V, only ∼58 mV deviation from Pt/C), high selectivity (electron-transfer number >3.95), and excellent electrochemical stability (only 9 mV negative shift of half-wave potential after 10 000 potential cycles). The unprecedented performance of these NPM catalysts in ORR was attributed to their well-defined porous structures with a narrow mesopore size distribution, high Brunauer–Emmett–Teller surface area (up to 572 m2/g), and homogeneous distribution of abundant metal–N x active sites.